L’animalità nella poesia di Jolanda Insana - Malicka, Paulina (Studia Romanica Posnaniensia, 2018)
The scope of the article is to reflect upon the argument of animality in the work of the Sicilian poet Jolanda Insana (1937-2016) which represents one of the possible interpretive keys of her works. The analytical part of the paper contains an analysis from the anti-anthropocentric perspective of some fragments of the section Bestia clandestina included in the volume Turbativa d’incanto (2012).